## Fibonacchi Series

Author: Iqbal Hossain

#### Problem

Let,
f(0) = 0;
f(1) = 1;
f(n) = f(n-1) + f(n-2)
How to implement it?

#### Solution

As I prefer python for code development. Problem function could be sloved in iterative or recurssion way. I have mention below only iterative way becouase of it is efficient.

Problem statement is produce fibonacchi series.

def f(n):
n0 = 0
n1 = 1
if n == 0:
return 0
elif n == 1:
return 1
elif n > 1:
for i in range(2, n+1):
# (n-1) + (n-2)
ni = n0 + n1
# forward cursor and update value
n0 = n1
n1 = ni
return "f(%s) = %s" %(n, ni)
else:
return -1
print(f(6))
Output:
f(6) = 8